1979
DOI: 10.1037/h0077619
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-induced polydipsia suppresses pituitary-adrenal activity in rats.

Abstract: The effects of schedule-induced polydipsia (SIP) on pituitary-adrenal activity, as indicated by plasma levels of corticosterone, were examined in a series of experiments. Male (Experiments 1 and 3) and female (Experiment 2) rats were reduced to 80% of their free-feeding weight and given daily sessions on an intermittent-feeding schedule (fixed time of 60 sec). Half of the subjects in each experiment had water available during experimental sessions, and the other half did not. Animals with water available in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 29 publications
(26 reference statements)
4
77
0
1
Order By: Relevance
“…Such conditions seem to be the common situations in which "schedule-induced adjunctive behavior" appears (Falk, 1977). A concomitant of such situations is a high level of pituitary-adrenal activity thatis quickly reduced when the adjunctive response (e.g., drinking) occurs (Brett & Levine, 1979). In our situation, the highly motivated response constrained by an externally imposed schedule and the species-typical response that can reduce the corticosterone level happen to be the same.…”
Section: Discussionmentioning
confidence: 74%
“…Such conditions seem to be the common situations in which "schedule-induced adjunctive behavior" appears (Falk, 1977). A concomitant of such situations is a high level of pituitary-adrenal activity thatis quickly reduced when the adjunctive response (e.g., drinking) occurs (Brett & Levine, 1979). In our situation, the highly motivated response constrained by an externally imposed schedule and the species-typical response that can reduce the corticosterone level happen to be the same.…”
Section: Discussionmentioning
confidence: 74%
“…All these environments may involve chronic conflict and frustration (Odberg 1978(Odberg , 1987b and hence stress (e.g. Falk 1971;Duncan & Wood-Gush 1974;Brett & Levine 1979), particularly if uncontrollable or unpredictable (e.g. Weiss 1971;Reynolds 1978;Herbert 1987).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the gastric ulceration developed by rats when forcibly restrained is significantly lower in animals that perform the apparently irrelevant displacement activity of biting an object (Vincent et al 1984). Adjunctive behaviour such as polydipsia (Brett & Levine 1979;Tazi et al 1986;Dantzer et al 1987) and chain-chewing by sows (Dantzer & Morm6de 1981) may also be accompanied by physiological signs of coping.…”
Section: Evidencementioning
confidence: 99%
“…Falk proposed that adjunctive behaviour may be related to displacement activities and hence to the frustration evident in a situation in which small periodic reinforcers are interspersed with long periods; events over which the subject has no control. It has even been suggested that schedule-induced polydipsia (SIP) may be a coping response, forming a strategy to minimise the frustration evident in this situation (Brett and Levine 1979). Either suggestion assumes that SIP arises from the induction of an aversive state in the subject which should be susceptible to treatment with anxiolytic drugs.…”
mentioning
confidence: 99%